Penggunaan Impor Sementara (Temporary Import) Menggunakan Ata Carnet Dalam Import Cargo MotoGP di Terminal Cargo Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Eka Ramdani Putra; Yunus Purnama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
MotoGP is an international motorcycle racing event that attracts global attention and impacts various sectors, including the logistics sector. One important aspect of the MotoGP event is temporary imports, such as motorcycles, spare parts, and supporting equipment. This study aims to explore how to handle temporary imports using ATA Carnet in MotoGP cargo imports and identify challenges and solutions during the MotoGP cargo handling process. The method used is qualitative, with primary data obtained through observations and interviews, and secondary data from written sources, films, images, and monumental works. The data analysis techniques applied include data reduction, data presentation, and drawing conclusions, with data validity tested using triangulation techniques and sources. The study results show that handling MotoGP cargo with temporary import status differs from general cargo, as it involves customs procedures and requires special documents such as ATA Carnet, Customs Notification of Special Economic Zones (PPKEK), and Temporary Import Permits for exemption from entry fees. The handling process must be performed quickly to save time, given the limited period for temporary imports before re-export. However, Customs personnel still face challenges related to the attachment of customs seals, so the company needs to evaluate the recruitment and training processes of workers. The solution is coordination between PT. Angkasa Pura Logistics and Customs for the addition of officers.